Environmental Sustainability and Organizational Commitment in Rainbow Trout Production in Junín, Peru: An Approach from Plithogenic Fuzzy Soft Sets - Manuel Michael Beraún-Espíritu; Ketty Marilú Moscoso-Paucarchuco; Humberto Dax Bonilla-Mancilla; Edson Hilmer Julca-Marcelo; Anani Basaldua Galarza; Jean Pierre Espeza-Gavilán; Lizve Vilcapoma Ureta; Jacqueline Denisse Llacza-Molina (Neutrosophic Sets and Systems)
Human resource management could leverage global environmental concerns to promote green practices. Furthermore, ecological sustainability is a major concern in modern society. Among other tools, the affective, normative, and continuance dimensions of organizational commitment are central to organizational implementation. This study aims to determine the relationship between environmental sustainability and organizational commitment in rainbow trout production in the Ingenio-Junín district. For data processing, we use the plithogenic soft set theory. On the one hand, plithogenic theory allows for the modeling of multidimensional phenomena with dynamics composed of elements of diverse origin, where each concept, its opposite, and its neutral are considered. Soft set theory effectively models the uncertainty inherent in data derived from human subjectivity. Plithogenic soft sets are the product of the hybridization of both concepts, which allows us to take advantage of the benefits of both tools. The study we propose to conduct depends on variables of diverse origin, having uncertainty in the measurements. This is why plithogenic soft sets are suitable for performing the proposed study.